Synthesis of Metal-Based Analogues of Isonicotinoyl and Benzoyl Hydrazones and Their Antioxidant and Cytotoxic Activities - Shafiq, Zahid; Hussain, Mazhar; Yaqub, Muhammad; Shafiq, Kiran; Ashraf, Mohammad; Badaruddin Ahmad, Hafiz (Asian Journal of Chemistry, 2012)
A series of 20 metal based [Cu(II), Co(II), Ni(II), Mn(II) and Zn(II)] compounds have been synthesized with novel 2,5-dihydroxyacetophenone isonicotinoyl hydrazone (L1) and 2,5-dihydroxyacetophenone benzoyl hydrazone (L2) Schiff bases and were screened for antioxidant and cytotoxic activities. All these complexes exhibited strong antioxidant activity against DPPH radical but no nitric oxide radical scavenging activity. Cytotoxicity assay showed toxicity at varied levels, that is, 1, 3, 7, 11, 15 showed maximum toxicity and 4, 9, 10, 12, 13, 16, 19, 20 showed minimal cytotoxicity against brine shrimp larvae. Antibacterial activity assay exhibited MIC50 values of 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 comparable to standard drugs for both gram-positive and gram-negative bacteria whilst other compounds showed minimal activity against these bacteria. Structure activity relationship shows the role of metal and the kind of complex associated with the said biological activities.